2016
DOI: 10.1088/0953-8984/28/24/244003
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental measure theory for non-spherical hard particles: predicting liquid crystal properties from the particle shape

Abstract: Hard-particle model systems help to improve our understanding of the effect of particle shape on collective behavior at a fundamental level. Furthermore, these system can now be realized in the form of colloids or nanoparticles due to recent advances in synthesis techniques [1]. A driving force for these efforts is the possibility that these experimental systems form structures that can be applied as novel materials. While these hard-particle systems were originally studied using computer simulations [2], the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 65 publications
0
45
0
Order By: Relevance
“…In order to improve the reliability of the present theory for confined plate-like particles, the dimensional cross-over between 2D and 3D systems should be incorporated correctly. Along this line the fundamental measure density functional theory can be a step ahead [68][69][70][71][72][73], which proved accurate for infinitely thin plates [74].…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the reliability of the present theory for confined plate-like particles, the dimensional cross-over between 2D and 3D systems should be incorporated correctly. Along this line the fundamental measure density functional theory can be a step ahead [68][69][70][71][72][73], which proved accurate for infinitely thin plates [74].…”
Section: Discussionmentioning
confidence: 99%
“…Onsager showed that the stability of the nematic phase is determined by a competition between the orientational entropy, which favours the formation of randomly oriented isotropic phases, and the packing entropy, which promotes the alignment of the particles by enhancing the free volume. Despite the success of Onsager's and subsequent density functional theories to describe the formation of liquid-crystalline phases in systems of lyotropic colloids [13][14][15][16][17][18][19][20][21][22][23][24][25], the first unequivocal observation of liquid-crystalline phases by essentially exact numerical computer simulation methods had to wait until the mid1980s. The pioneering computer simulations of Frenkel and co-workers for systems of hard anisotropic particles confirmed the earlier theoretical predictions of the formation of not only nematic and discotic orientationally ordered phases in rod-like and disc-like particles but also of stable smectic (layered) and columnar (stacked) phases [1,11,[26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] FMT has been successfully applied to polyhedra with moderate shape anisotropy. 29 More recent advances, 30,31,33 after which the smectic phase of rods can be described, were not implemented in Ref. 29 The existence of polyhedral nanorods 3,[34][35][36] and the observation of smectic-like ordering of these rods 34,35 motivated us to consider the effect of polyhedral shape on the liquidcrystal phases of rod-like particles.…”
Section: Introductionmentioning
confidence: 99%